Եղիշէ Չարենցի վերջին տարին - Գասպարեան, Դաւիթ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье в хронологическом порядке представлен последний год жизни армянского гения – Чаренц, находящегося в капкане репрессий, ведущих к гибели. Гонения на Чаренца усилились в 1933 году в связи с запретом издания «Книги пути», которая в итоге с изменениями вышла в свет в 1934 году. В 1935 году он неоднократно подвергался допросам, а в день своего рождения, 13 марта, был исключен из Союза писателей. В 1937 году преследования усилились. Чаренца обвинили в национализм и арестовывали 27 июля 1937 года. Допросов не было. Поэт умер в нечеловеческих условиях тюрьмы 27 ноября 1937 года. За это время он написал много стихов. Представлена литературная среда, в которой жил и творил Чаренц. Это была обстановка политического мошенничества, обусловленная деятельностью Сталина-Берии, планом последующего приговора политического руководства Армении (Ханджяна, Аматуни) к смертной казни. За это время литературные силы были уничтожены, а расстрелы и депортации стали обычным явлением. Чаренц умер в тюрьме. Местонахождение его могилы до сих пор неизвестно. The article chronologically presents the last year of the life of Charents, unfortunate Armenian genius. He is portrayed in the trap of repressions that lead to death. Persecutions against Charents had been intensified as early as in 1933 in connection with the ban on the publication of the book “Book of the Road”. Finally, the book was published with changes in 1934. In 1935, he was repeatedly interrogated, and on his birthday, March 13, he was expelled from the Writers’ Union. In 1937, the persecutions were intensified even more. Charents was accused of being a nationalist, and was arrested on July 27, 1937 without any interrogation. He died in inhuman conditions of prison on November 27, 1937. During this period, he wrote many poems. The article presents the literary environment, in which Charents lived and created. It was an environment of political fraud, conditioned by the activities of Stalin and Beria, with a plan to subsequently sentence the Armenian political leadership (Khanjyan, Amatuni) to death. During that period, literary figures were massacred; executions and deportations became ordinary. Charents died in the prison of Yerevan; his burial place is unknown.
Keywords: Գրական գործիչներ; Կենսագրութիւն